Morbidity Pattern and Profile of Patients Attended at the Private Chamber of a Practicing Psychiatrist (KYAMC Journal, 2017)
Mental illnesses are of various types and all of them have a great impact on the life of the Sufferer, family members and on the society. This study was conducted by the author in the middle of 2002 to find out types of mental illness prevailing in the community on the patients attended at his private chamber. Total eighty new cases were attended during the study period. A semi structured questionnaire was used to collect relevant data and Mental State Examination was done by the author during clinical interview. Majority of the patients belonged to 11 to 30 year age group. Males were 65% and the rest were females. Muslims and Hindu patients were 86.25 and 13.75% respectively. A good number (11.25%) of the cases were married before 18 years of age and 22.50% had a family history of mental illness. Two-thirds of the cases were from rural background. Psychotic patients were 51.25%. Patients having Mental retardation, Headache and Psychoactive substance use disorder also present. Urban patients suffer more than rural. Findings of this may be helpful in assessing the present disease situation in our community.KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 371-379